TANGGAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA PEMBIBITAN UTAMA MEDIA TANAH GAMBUT ATAS PEMBERIAN PUPUK HAYATI MIZA PLUS DAN KOMPOS TANDAN KOSONG KELAPA SAWIT - R, Rahman; H, Panupesi; A, Syahid (Fakultas Pertanian Universitas Palangka Raya, 2015)
The objective of the research is to study : a) the interactions between biological fertilizer of Miza Plus and compost of oil palm empty bunches on the growth of main nursery oil palm seedlings in peat soil, b) the growth response of main nursery oil palm seedlings by applying biological fertilizer of Miza Plus and, c) the growth response of main nursery oil palm seedlings by applying of oil palm empty bunches compost in peat soil media. Experimental design used was Completely Randomized Design (CRD) consisted of two factors. The first factor was application of 4 levels biological fertilizer of Miza Plus namely 0, 20, 40 dan 60 g polibag-1and the second factor was the provision of 4 levels composting of oil palm empty bunch namely 0.25; 0.50; 0.75 kg polibag-1. The results showed that the interaction only occurs on height of plant at the age of 10 and 12 week after planting by applying biological fertilizer of Miza Plus of 40 g polybag-1 and 0.50 kg polybag-1 of oil palm empty bunch compost. Application of 40 g polybag-1 had a significantly increased number and length of roots, mean while 0.25 kg polibag-1 oil palm empty bunch had significantly increased on the number of fronds, stem diameter and fresh weight of plant